A molecular investigation of stem-galling Tetramesa Walker (Hymenoptera: Eurytomidae) on African grasses: applications to biological control - Van Steenderen, Clarke Julian Mignon (Rhodes University, Faculty of Science, Department of Zoology and Entomology)
South Africa is a larger donor than receiver of alien grasses, where approximately 15% (_ 165 spp.) of the country's native grass species have become naturalised elsewhere. Many of these grasses have become serious invaders, causing significant damage to native species, habitat structure, and ecosystem functioning. Biological control is a sustainable and cost-effective method for the control of invasive weeds, but its application to invasive grasses has been approached with trepidation in the past due to the fears of a lack of host-specific herbivores that may cause non-target damage to agriculturally-important crops. The Tetramesa Walker genus (Hymenoptera: Eurytomidae) is one of three genera in the family that feed exclusively on grasses, and have a record of being host-specific to a particular species, or complex of closely-related congeners. There are over 200 described Tetramesa species, but this taxonomic effort has occurred almost exclusively in the Northern Hemisphere. Only about 2% of the described species are from Africa, with none from southern Africa despite the high diversity of grasses in the region. The low morphological variability between many Tetramesa groups has made identification difficult, where there may in fact be multiple undiscovered cryptic species. This thesis generated genetic sequence data (mitochondrial COI and nuclear 28S) that revealed at least eight native southern African Tetramesa taxa that are new to science, focusing particularly on the assemblages associated with Eragrostis curvula Nees (African lovegrass) and Sporobolus pyramidalis Beauv. and S. natalensis Steud. (giant rat's tail grass) which are alien invasive pests in Australia. Approximately 200 eurytomid wasps were collected and sequenced from 19 grass species across six South African provinces. Additionally, 27 grass species were sequenced using four gene regions (rps16-trnK, rps16, rpl32-trnL, and ITS), which were added to existing sequence data to build a dataset comprising over 700 sequences. Field host ranges and the use of host grass genetic proxies were important in making inferences about the host-specificity of eurytomid wasps of interest. Nine Tetramesa groups appeared to be host-specific to a single grass species, while six Tetramesa were associated with multiple species in a single grass genus. Since S. pyramidalis, S. natalensis, S. africanus, Hyparrhenia hirta, E. trichophora, and Andropogon gayanus are weeds elsewhere, there are at least six potential Tetramesa biological control agents that have been identified. A high diversity of Tetramesa on grasses within the Eragrostis genus was reported, with at least four taxa associated with E. curvula. It is currently uncertain whether these taxa represent different cryptic species or intraspecific populations that are the result of geographic sub-structuring. No-choice host-specificity testing using Tetramesa sp. 4 on E. curvula revealed that the wasp could complete its lifecycle on two non-target African grasses; namely E. plana and E. planiculmis. The wasp was also recorded on other Eragrostis species in the field (namely E. biflora and E. capensis). Using grass genetic sequences obtained in this study, it was found that there are four native Australian Eragrostis species that are more closely related to target E. curvula than to the non-target E. plana and E. planiculmis. This suggests that Tetramesa sp. 4 may not be suitably host-specific for use as a biological control agent. Further host-specificity testing on these native Australian species is required, however, before this insect is ruled out completely. The Tetramesa on S. pyramidalis (Tetramesa sp. 1), and the unidentified Sporobolus species presumed to be S. africanus, were suitably host-specific to be used as biological control agents. Since it was unclear whether some phylogenetic clades were true species or intraspecific populations, which is essential to understand when selecting agents for biological control, a new piece of software, SPEDE-sampler", was developed. It offers users of the Generalised Mixed Yule Coalescent (GMYC) species delimitation model a means of assessing the degree to which sampling effects such as data size and parameter choice can influence species diversity estimates. When applied to the Tetramesa data set, the software assisted in identifying which groups may contain cryptic species, uncovering that the COI marker is affected more by singletons than the 28S marker (i.e. species diversity tends to be overestimated), and confirming putative Tetramesa taxa that could be useful for biological control programmes going forward. This thesis has provided evidence that South Africa contains a diverse assemblage of Tetramesa and other eurytomids that are closely associated with their grass hosts, and that many of these taxa hold promise for grass biological control. This work has also highlighted the importance of integrative taxonomy in the discovery of novel taxa, and that biological control practitioners need to be aware of the caveats of each line of evidence used in the delimitation of putative species.
Keywords: Grasses Africa; Tetramesa; Invasive plants -- Biological control; DNA barcoding; Weeds -- Biological control; Eragrostis curvula; Sporobolus pyramidalis; Sporobolus natalensis